(untitled) (Experimental biology, 2015)
In this research were selected strong sort Asem, Saule and sensitive sort Odesskaya-100. The research work investigated individual and combined effect of copper ions and salt on the comparative amount of water in the leaves of barley.In combined action of copper ions and salts comparative amount of water in the leaves decreased significantly than in their individual action.